Lucrative religion prize given: The Templeton winner, Holmes Rolston 3d, is credited for his push on environmental ethics - Remsen, Jim, author; Philadelphia Newspapers, Inc., publisher (Colorado State University. Libraries, 2003)
Interview citing Dr. Rolston's career and contributions to the study of nature, environmental ethics, and the relationship between science and religion.
Keywords: philosophy professor; Rolston, Holmes, 1932-2025; Templeton Prize; Colorado State University